Pengembangan Keterampilan Berpikir Inventif Siswa Sekolah Dasar melalui Pembelajaran Ilmu Pengetahuan Alam (IPA) - Wijaya, I Komang Wisnu Budi; Yasa, I Made Wiguna; Darmayanti, Ni Wayan Sri (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to analyze efforts to develop inventive thinking skills through science learning in elementary school students. This research is classified as library research. Data comes from literature related to inventive thinking abilities, science learning and elementary school students. After the data is collected and sorted, analysis techniques are carried out using content analysis techniques. The results of the research state that inventive thinking abilities can be developed in science learning by applying varied learning, open questions, applying independent learning and contextual and student-centered science learning. The teacher's role is as a learning designer, motivator and evaluator.